Does political connectedness determine stock returns in Indonesia? - Endang Dwi Astuti; Yunieta Anny Nainggolan (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This study aims to investigate the influences of political connection on stock returns in Indonesia. We develop a comprehensive database of firm-level political connectedness among Indonesian firms from 2010 to 2017. Our sample is non-financial Indonesian listed firms that are selected in the Kompas 100 index for 16 consecutive periods, with a total of 448 firm-year observations. This study employs panel data regressions to estimate this relationship, then mitigate possible endogeneity issues using two-stage least square with fixed-effects. The finding of this study shows that political connectedness is associated with lower stock returns, more prominently in agriculture and consumer goods industries. Moreover, state-owned enterprises are more likely to earn lower stock returns. In summary, our result suggests that investing in politically connected firms could be a risky investment. The finding holds using alternative estimation methods